Travel Burden and the Direct Medical Costs of Urologic Surgery - Daniel J. Olson; John L. Gore; Kenn B. Daratha; Kenneth P. Roberts (Journal of Health Economics and Outcomes Research)
# Background Increased surgical volume is associated with better patient outcomes and shorter lengths of hospitalization. As a consequence, traveling to receive care from a high volume provider may be associated with better outcomes. However, travel may also be associated with a decision by the healthcare provider to increase the length of stay due to a decreased ability to return to the primary hospital should complications arise. Thus, research is needed to understand the relationship between the distance a patient must travel and their outcomes following urologic surgery.